SEKAR RARE SEBAGAI MEDIA PEMBELAJARAN NILAI ETIKA HINDU DI PENDIDIKAN ANAK USIA DINI - Wiasti, Ni Komang (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Dharmagita is a sacred religious song that is sung during religious ceremonies. Within a specific scope, Dharmagita can be sung at the level of formal, non-formal and informal education. Because the benefits are very important for Hindus, and even used to accompany dances that are profane and sacred, children's play, and even worship to Ida Sanghyang Widhi wasa. Sekar rare as a children's song that has a cheerful character, as an accompaniment to children's games today needs to be raised from an early age to an adult level, with the aim of fostering social sensitivity, courtesy, sradha bhakti, as Hindu ethical values. In reality, it is rarely used by PAUD teachers because of the lack of references, and they are still focused on implementing a complete curriculum, so it needs to be awakened. Therefore, it is necessary to study about sekar rare as a medium for learning Hindu ethical values in PAUD. The method used in the meaning of rare sekar is qualitative descriptive. Data analysis refers to interpretive data and facts. There are several Hindu ethical values contained in Dolanan, Gending Janger, and Gending Sanghyang, namely divine values, compassion values, national values, sradha bhakti values, and social values.